Production and characterization of neutralizing and nonneutralizing monoclonal antibodies against listeriolysin O. - Nato, F (1991)
Listeriolysin O (LLO) is a thiol-activated toxin secreted by the facultative intracellular pathogen Listeria monocytogenes. LLO is essential for the survival of the bacterium in the infected cell because it promotes lysis of the phagosome membrane and escape of the bacterium into the cytosol. LLO was used as an antigen for the production of nine monoclonal antibodies (MAbs) in mice. Three of these could inhibit the hemolytic activity of LLO. One of them inhibited binding of LLO to erythrocyte membranes. The two other antibodies blocked the activity of LLO at a step subsequent to membrane binding. Only two of the nine MAbs recognized three other purified SH-activated toxins, streptolysin O, alveolysin, and pneumolysin. Western blot (immunoblot) analysis of culture supernatants of Listeria ivanovii and Listeria seeligeri, two hemolytic species of the genus Listeria, revealed that two MAbs recognized ivanolysin and seeligerolysin. The latter was also recognized by two other MAbs, including one of the neutralizing antibodies. MAbs raised against a peptide, ECTG LAWEWWR, present in all thiol-activated toxins sequenced to date, recognized all toxins and were not neutralizing. Taken together, these results demonstrate the existence of regions important for hemolytic activity that are unique to hemolysins of the genus Listeria and show that regions outside the conserved peptide are important for activity of LLO.